2019
DOI: 10.1128/aem.02803-18
|View full text |Cite
|
Sign up to set email alerts
|

A Lytic Polysaccharide Monooxygenase from a White-Rot Fungus Drives the Degradation of Lignin by a Versatile Peroxidase

Abstract: Lytic polysaccharide monooxygenases (LPMOs), a class of copper-dependent enzymes, play a crucial role in boosting the enzymatic decomposition of polysaccharides. Here, we reveal that LPMOs might be associated with a lignin degradation pathway. An LPMO from white-rot fungus Pleurotus ostreatus, LPMO9A (PoLPMO9A), was shown to be able to efficiently drive the activity of class II lignin-degrading peroxidases in vitro through H2O2 production regardless of the presence or absence of a cellulose substrate. An LPMO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 68 publications
(86 reference statements)
0
33
0
Order By: Relevance
“…Electron donors include lignin-derived compounds released during biodegradation, diphenols produced by the reaction of different AA3, and by cellobiose dehydrogenases (AA8) [ 65 ]. A recent study has shown that H 2 O 2 generated by LPMO was favorably used for lignin oxidation by the lignin-degrading peroxidases rather than for cellulose oxidation [ 66 ]. The induction of LPMO and their coupled secretion with AA3_1 support their role in lignin modification.…”
Section: Resultsmentioning
confidence: 99%
“…Electron donors include lignin-derived compounds released during biodegradation, diphenols produced by the reaction of different AA3, and by cellobiose dehydrogenases (AA8) [ 65 ]. A recent study has shown that H 2 O 2 generated by LPMO was favorably used for lignin oxidation by the lignin-degrading peroxidases rather than for cellulose oxidation [ 66 ]. The induction of LPMO and their coupled secretion with AA3_1 support their role in lignin modification.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, lignin-active enzymes can affect the electrondonating and H 2 O 2 -generating abilities of lignin, providing possible links between polysaccharide-and lignin-degrading enzyme systems [42,115,269]. Another possible link between these systems is that LPMO-facilitated in situ production of H 2 O 2 may be utilized by peroxidases to degrade lignin [213].…”
Section: Lpmos and Catalasesmentioning
confidence: 99%
“…The auto oxidation of reductants by O 2 often leads to the formation of H 2 O 2 and this complicates the interpretation of kinetic data. Furthermore, LPMOs that are free from substrate have both reductant oxidase 23 and peroxidase 16,18 activity where the oxidase activity leads to the formation of H 2 O 2 17,[23][24][25] .…”
mentioning
confidence: 99%